Electoral Authoritarianism in Indonesia: The Legal and Political Machinery Behind Indonesia’s 2024 Election - Karim, Zahlul Pasha (Indonesian Journal of Law and Society, 2025)
This study examines the phenomenon of electoral authoritarianism in Indonesia through the lens of the 2024 presidential election victory of the Prabowo-Gibran ticket. Using a descriptive qualitative method, this research analyzes data from mass media and NGO reports to uncover how state power was strategically deployed to benefit one candidate. The findings reveal three core manifestations of electoral authoritarianism: (1) presidential intervention through policies, statements, and political actions in favor of Prabowo-Gibran; (2) active involvement of government officials—including ministers and regional leaders—in campaign activities; and (3) repression of opposition candidates via administrative obstructions and permit cancellations. These practices, although formally legal, violate democratic ethics and principles of electoral fairness, illustrating how legal frameworks were manipulated to maintain regime power while maintaining a façade of democratic legitimacy. The study concludes that Indonesia is experiencing democratic backsliding, marked by executive aggrandizement and strategic manipulation of elections—hallmarks of competitive authoritarian regimes that undermine the democratic process while preserving its superficial mechanisms.